The Risk of Landslides on Building Land Use in Tajum Hulu Sub-Watershed in Banyumas Regency - Haris Yudha Prasetya; S Suwarno; Esti Sarjanti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Land use is a processed product or the result of human actions on land that aims to meet every life need. This study aimed to determine the risk of landslides in the use of building land in the Tajum Hulu Sub-watershed, Banyumas Regency. Surveys were used as the method of study. The data consisted of secondary and primary data, in the form of vulnerability and loss data. Descriptive quantitative data analysis with spatial analysis was conducted in order to determine the correlation between building land use and the risk of landslides. The results showed that the risk of landslides on building land was different from the widest tothe narrowest including medium risk with an area of 18980 ha or 73.1%, high risk with an area of 2583 ha or 10%, and low risk with an area of 4385 ha or 16.9%.